Impact of Information Booklet on Harmful Effect of Use of Plastics in Relation to Practices among Urban Resident of Pune - Greety Paul1 , Nakabuye Sharifah1 , Rupali Bhujbal1 , Shruti Thorat1 , Sonopant.G Joshi2 , Ranjana C (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Plastics are a wide variety of combinations of properties when viewed as a whole. They areused for variety of items and the list could go on and on and it is obvious that much of what we have todaywould not be possible without plasticsMaterial and Methods: An experimental study was conducted on practice of community regardingharmful effects of plastics among urban residents of Pune city. The pre-experimental design was adoptedand 40 samples were selected through simple random sampling technique. The data was obtained from theparticipants using an interview method which included details on socio-demographics of the participants,practice of plastics. The same Questionnaire were administered after providing informational booklet aswell.Result: The findings revealed that practice of people regarding the harmful effect of the use of plastics was45.65 % whereas Post –test score of the practice was 55.11 %, the practices in t-Test at 0.05 level hence thebooklet in improving practice needs more hammering among the urban residents.